Answers to life's difficult questions : encouragement for your most common fears and struggles - Warren, Rick (Singapore IMprint, 2006)
In this book are practical steps and specific actions you can take, based on God's Word, that will help you cope with 12 of the most difficult, perplexing challenges, struggles, and fears we all face: How can I cope with stress? How can I rebound from failure? How can I overcome depression? How can I live to my full potential? How can I have peace of mind? How can I handle discouragement? How can I tackle my problems? How can I be confident in a crisis? How can I ever change? How did l get myself into this mess? How can I conquer loneliness? Why is this happening to me?
Keywords: Christian life. Adjustment (Psychology) -- Religious aspects -- Christianity